Redesign of a GI endoscopy unit during the COVID-19 emergency: A practical model. Issue 10 (October 2020) - Cennamo, Vincenzo; Bassi, Marco; Landi, Stefano; Apolito, Pasquale; Ghersi, Stefania; Dabizzi, Emanuele; Polifemo, Anna Maria; Gizzi, Giuseppe; Guicciardi, Stefano; Indelicato, Giuseppe; Cascone, Carmelo; Tovoli, Daniele; et al.
ABSTRACT: The pandemic diffusion of the SARS-CoV-2 infection throughout the world required measures to prevent and strategies to control the infection, as well as the reallocation of the hospital structures in order to take care of an increased number of infected patients. Endoscopy Units should be able to perform endoscopic procedures on COVID-19 infected as well as on noninfected patients. The aim of this manuscript is to propose a model for a fast reorganization of the endoscopy department environment in order to safely perform endoscopic procedures in this Pandemic COVID-19 scenario, according to the current advices given by the Scientific Societies